2021
DOI: 10.3390/biom11020185
|View full text |Cite
|
Sign up to set email alerts
|

Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: The Human Herpesviruses Are Back!

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) or Systemic Exertion Intolerance Disease (SEID) is a chronic multisystem illness of unconfirmed etiology. There are currently no biomarkers and/or signatures available to assist in the diagnosis of the syndrome and while numerous mechanisms have been hypothesized to explain the pathology of ME/CFS, the triggers and/or drivers remain unknown. Initial studies suggested a potential role of the human herpesviruses especially Epstein-Barr virus (EBV) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 125 publications
(170 reference statements)
0
69
0
6
Order By: Relevance
“…There are studies showing a statistically significant elevation of anti-EBV-dUTPase antibodies (75,76), a defective EBV-specific B and T cell response (77), a high rate of active EBV infection (28), serologic evidence of EBV reactivation with elevated IgM antibodies against late VCA antigen (78-80), and a positive up-regulation of EBV-induced gene 2 (EBI2) mRNA in peripheral blood mononuclear cells (PBMC) (3) from a subgroup of patients with ME/CFS. However, serological observations related to EBV were not always confirmed and, accordingly, the association between EBV infection and ME/ CFS is not established (81)(82)(83)(84)(85). Furthermore, the presence of an active EBV infection in a subgroup of ME/CFS patients has been actively debated, because most studies revealed no increase in EBV viral load in ME/CFS patients.…”
Section: A Hypothetical Association Between Ebv and Me/cfsmentioning
confidence: 99%
“…There are studies showing a statistically significant elevation of anti-EBV-dUTPase antibodies (75,76), a defective EBV-specific B and T cell response (77), a high rate of active EBV infection (28), serologic evidence of EBV reactivation with elevated IgM antibodies against late VCA antigen (78-80), and a positive up-regulation of EBV-induced gene 2 (EBI2) mRNA in peripheral blood mononuclear cells (PBMC) (3) from a subgroup of patients with ME/CFS. However, serological observations related to EBV were not always confirmed and, accordingly, the association between EBV infection and ME/ CFS is not established (81)(82)(83)(84)(85). Furthermore, the presence of an active EBV infection in a subgroup of ME/CFS patients has been actively debated, because most studies revealed no increase in EBV viral load in ME/CFS patients.…”
Section: A Hypothetical Association Between Ebv and Me/cfsmentioning
confidence: 99%
“…In this regard, a large proportion of patients report an acute infection at the onset of their symptoms ( 22 , 23 ). Herpesviruses such as the Epstein-Barr virus (EBV) and the human herpesvirus-6 (HHV6) were considered to be the main candidates for the causative agents of ME/CFS due to their high prevalence in adults and their reactivation observed in patients ( 11 , 24 , 25 ). To understand the role of these viruses on ME/CFS, many serological investigations were conducted with inconclusive or even contradicting findings ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although its cause remains unknown, a growing body of evidence strongly associates ME/CFS with several microbial and viral infections, as potential trigger factors 3 , 4 . In addition, it has been hypothesized that reactivations of latent viral infections also play a role 5 , 6 due to several abnormalities at the level of the immune system 7 , 8 , 9 . On the molecular basis of the disease, peripheral blood mononuclear cells (PBMCs) show altered gene expression profiles [ 10 ], including a decreased abundance of the human angiotensin-converting enzyme 2 (ACE2) [ 11 ], the main cell entry receptor of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) 12 , 13 , 14 .…”
Section: Introductionmentioning
confidence: 99%